Keanekaragaman Tumbuhan Paku Di Kawasan Twa Kerandangan Kabupaten Lombok Barat - Hidiyatul Fithi; Siti Diana Fathia; Hasan Basri; Ervina Titi Jayanti (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2024)
Kerandangan Nature Tourism Park is a conservation area located in Senggigi village, West Lombok. Exotic landscapes and a variety of flora and fauna are the characteristics that distinguish this tourist park. The type of research used is descriptive qualitative research, aiming to obtain data and information that contains a description of the diversity of ferns in the Kerandangan TWA area. The sampling technique used the roaming method in combination with plots, namely by exploring the TWA area from the front yard to the Goa Walet waterfall and making plots measuring 5m x 5m for each station where fern data were collected. The data analysis technique uses a quantitative descriptive method, namely calculating the IVI and H´ of ferns obtained, and documentation. The results showed that it was in the Kerandangan TWA area. The results showed that there were 13 species of ferns including Adiantum raddianum C. Presl, Christella dentata (Forssk.) Brownsey & Jermy, Cystopteris fragilis (L.) Bernh., Elaphoglossum crassifolium (Gaudich.) W.R. Anderson & Crosby, Microsorum pustulatum (G. Forst.) Copel., Nephrolepis biserrata, Odontosoria chinensis (L.) J.Sm., Platycerium bifurcatum C. Chr, Polypodium vulgare, Pteridium aquilinum (L.) Kuhn, Pteris biaurita L. , Pteris ensiformis Burn., Selaginella sp. Based on the results of data analysis, it was found that the IVI at station 1 was dominated by C. fragilis (63.17%), C. dentata (51.03%), and A. raddianum (45.95%). The IVI at station 2 was dominated by P. aquilinum (56.14%), and the IVI at station 3 was dominated by E. crassifolium (97.57%) and Selaginella sp (53.22%). The index value of fern diversity in Kerandangan TWA proves that the diversity of fern species from each station is in the medium category with a value of 1.0 < H´ <3 where H´ at station 1 is 1.70, station 2 is 1.69, and station 3 is 1.24.